Utilization of Patin Bone Flour (Pangasius hypopthalmus Sp.) As an Additional Biscuit For Stunting Children - Siagian, Dewi Sartika; Sidoretno, Wahyu Margi; Kartini, Sri (Universitas Aisyah Pringsewu, 2020)
Stunting is one of the nutritional problems in Indonesia, the direct causes of stunting are infectious diseases and inadequate food intakes, such as protein and calcium deficiency. Calcium is a macromineral that is needed by humans and has an important role and function for the body, both in cells, tissues, organs and the whole body. Sources of calcium can be obtained from daily food or foods that are intentionally added calcium to increase its nutritional value. One of the easiest and cheapest food sources to obtain is fish, such as ikan patin (Pangasius hypothalamus Sp.). Ikan patin is a fish that is classified as delicious, delicious and tasty fish. In addition, ikan patin contains high protein and low cholesterol. The aim of this research is to produce biscuits made from ikan patin bone meal which has great potential to be used as raw material for a bone meal which is rich in calcium. This type of research is experimental. The procedure of this research was carried out in two stages, namely making fishbone meal from ikan patin and making biscuits with the addition of fishbone meal with various concentrations of 0 percent, 25 percent and 50 percent. The results showed that the levels of calcium in the biscuits with the addition of ikan patin bone meal with various concentrations were 1.3 percent, 5.39 percent, 5.95 percent, the biscuit protein content of each concentration was 2.59 percent, 4.74 percent and 4.71. percent. The results of this study can be used as a reference in making food with the addition of ikan patin bone meal which is rich in calcium levels.Abstrak: Stunting adalah salah satu permasalahan gizi di Indonesia, penyebab langsung stunting adalah penyakit infeksi dan asupan makanan yang tidak memadai, seperti kekurangan protein dan kalsium. Kalsium merupakan makromineral yang dibutuhkan oleh manusia dan memiliki peran dan fungsi penting bagi tubuh, baik pada sel, jaringan, organ dan keseluruhan tubuh. Sumber kalsium dapat diperoleh dari makanan sehari-hari atau makanan yang sengaja ditambahkan kalsium untuk meningkatkan nilai gizinya. Salah satu sumber makanan yang paling mudah dan murah untuk didapatkan adalah ikan, seperti ikan patin (Pangasius hypopthalmus Sp.). Ikan patin merupakan ikan yang tergolong ikan enak, lezat dan gurih. Disamping itu, patin mengandung protein yang tinggi dan kolestrol yang rendah. Tujuan dari penelitian ini untuk menghasilkan biskuit yang terbuat dari tepung tulang ikan patin yang memiliki potensi besar untuk dimanfaatkan sebagai bahan baku tepung tulang yang kaya akan kalsium. Jenis penelitian ini adalah eksperimental. Prosedur penelitian ini dilakukan melalui dua tahap yaitu pembuatan tepung tulang ikan dari ikan patin dan pembuatan biskuit dengan penambahan tepung tulang ikan dengan berbagai konsentrasi 0 persen, 25 persen dan 50 persen. Hasil penelitian menunjukkan kadar kalsium pada biskuit dengan tambahan tepung tulang ikan patin dengan berbagai konsentrasi tersebut adalah 1,3 persen, 5,39 persen, 5,95 persen , kadar protein biskuit masing-masing konsentrasi adalah 2,59 persen, 4.74 persen dan 4.71 persen. Hasil penelitian ini dapat dijadikan referensi dalam pembuatan makanan dengan tambahan tepung tulang ikan patin yang kaya akan kadar kalsium.